The Influence of Social and Lifestyle Factors on Buying Interest in Fashion at Thrift Shops in Kolaka Regency - Lista, Lista; Titing, Andry Stepahnie; Zul Bay, Agus (PROCURATIO: Jurnal Manajemen & Bisnis, 2025)
Purpose – This study aims to examine the influence of social factors and lifestyle on consumers’ buying interest in fashion products at thrift shops in Kolaka Regency, Indonesia. Addressing a gap in prior research, this study focuses on a non-metropolitan context where empirical evidence on second-hand fashion consumption remains limited. Design/method/approach – A quantitative explanatory research design was employed. Data were collected from 100 thrift shop consumers in Kolaka Regency using purposive sampling. A structured questionnaire was administered to capture respondents’ perceptions of social factors, lifestyle, and buying interest. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.0 to assess the relationships among the studied variables. Findings – The findings reveal that both social factors and lifestyle have a positive and statistically significant effect on buying interest in thrift fashion products. Social factors, including peer influence, family recommendations, and perceived social recognition, play a substantial role in shaping consumers’ purchase intentions. In addition, lifestyle dimensions—such as activities, interests, and opinions—significantly contribute to consumers’ inclination toward thrift shopping, indicating that thrift fashion aligns with personal values and daily consumption practices. Implications – The results of this study provide practical and managerial implications for thrift shop entrepreneurs and fashion marketers, particularly in non-metropolitan and emerging market contexts. Understanding that buying interest is strongly influenced by social interactions and lifestyle orientation enables businesses to design more targeted marketing strategies, such as community-based promotions, peer-driven campaigns, and lifestyle-oriented branding. Policymakers and local creative economy stakeholders may also use these insights to support sustainable consumption initiatives by promoting second-hand fashion as an economically accessible and environmentally responsible alternative. Novelty/Originality –This study provides empirical evidence on thrift fashion buying interest in a rural Indonesian context, integrating social and lifestyle perspectives rarely examined jointly.